2010
DOI: 10.1111/j.1365-2702.2010.03488.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of symptom severity on the relationship between self‐efficacy for exercise and depression

Abstract: AimThe aim of this study was to determine the relationship between symptom severity, self-efficacy for exercise and depression in heart transplant recipients in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…29 A recent meta-analysis found that most of reviewed studies reported a significant relationship between coronary heart disease outcomes and depression. 33 The results of this cross-sectional study showed that for every 1-unit increase in symptoms of depression, there was a corresponding 1-unit decrease in ESE. For example, patients who entered CR with major depressive disorder were more likely to discontinue the program than were patients without major depressive disorder.…”
mentioning
confidence: 75%
“…29 A recent meta-analysis found that most of reviewed studies reported a significant relationship between coronary heart disease outcomes and depression. 33 The results of this cross-sectional study showed that for every 1-unit increase in symptoms of depression, there was a corresponding 1-unit decrease in ESE. For example, patients who entered CR with major depressive disorder were more likely to discontinue the program than were patients without major depressive disorder.…”
mentioning
confidence: 75%